Factors Influencing the Intention to Use Touch and Go E-Wallet Among Malaysian Citizens - Yew, Lim Kim; Chen, Yang; Husni, Akmal; Fei, Goh Chin; Kowang, Tan Owee; Wei, Zhang; Udang, Lester Naces (Journal of Posthumanism, 2025)
This study examines the factors influencing the intention to use the Touch n Go e-Wallet among Malaysian citizens, as online payment methods have gained popularity due to technological advancements. The research investigates the impact of individual variations on perceived ease of use, as well as the influence from features of mobile payment systems on perceived usefulness and perceived ease of use, all with regards to the intention to use the Touch n Go e-Wallet. The study gathered responses from 166 participants in Malaysia through a questionnaire distributed via social media platforms and analyzed the data using Statistical Package for Social Science (SPSS), structural equation modeling (SEM), and partial least squares (PLS) or SmartPLS 4.0 software. The findings reveal that individual variations have a negative effect on perceived ease of use, while the features of mobile payment systems have a positive impact on perceived usefulness and perceived ease of use, ultimately influencing the intention to use the Touch n Go e-Wallet. The study’s results can benefit both users and the company, as users can conveniently utilize the service for transactions, and the company can improve its product innovation and services to meet customer needs and maintain competitiveness in the market.